Własności i prawa przyrody w esencjalizmie dyspozycyjnym - Wodzisz, Rafał (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2011)
The aim of this paper is to articulate dispositonal essentialism (DE) as a viable position in the discussions considering properties and laws of nature. In the first part of the article there are given several "must have" trades of properties in DE. They are followed by the conceptions themselves. The last part of the article brings a little insight about ceteris paribus laws in DE.